2015
DOI: 10.1111/his.12787
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of intestinal stem cell markers in colorectal precancerous lesions

Abstract: The expression and distribution profile of ISC markers possibly provides insights into the organization of stem and progenitor-like cells in each type of precancerous lesion of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…OLFM4 is generally expressed in the basal crypt cells and is considered as a specific stem cell protein [3135]. It is involved in cancer development via antiapoptotic action, in cell proliferation, cell adhesion and metastasis [3638].…”
Section: Discussionmentioning
confidence: 99%
“…OLFM4 is generally expressed in the basal crypt cells and is considered as a specific stem cell protein [3135]. It is involved in cancer development via antiapoptotic action, in cell proliferation, cell adhesion and metastasis [3638].…”
Section: Discussionmentioning
confidence: 99%
“…Using previously described protocols, RNA in situ hybridizations (ISH) for GREM1 were performed on 10 TMAs with the RNAscope FFPE assay kit (Advanced Cell Diagnostics, Inc., Hayward, CA, USA) [17]. Briefly, 4-μm TMA sections were baked at 60°C for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…Additional markers for CBC stem cells include Achaete-Scute homologue 2 (Ascl2) 15 , SPARC-related modular calcium-binding 2 (Smoc2) 16 , Prominin 1(Prom1) 17 , Musashi homologure 1 (Msi1) 18 , Olfactomedin 4 (Olfm4) 19 , and EphB2 20 . Of these, subsequent studies found that the expression of Prom1 21 , Msi1 22 , Olfm4 23 , and Ephb2 23 extends to the transit amplifying cells. Markers of +4 stem cell population are Bmi1, Homeodomain-only (Hopx), Leu-rich repeats and immunoglobulin-like domains 1 (Lrig1), and telomerase reverse transcriptase (Tert) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Most sporadic colorectal cancers in humans also arise from the mutations in the adenomatous polyposis coli ( APC ) gene, and overexpression of stem cell markers has been demonstrated in the sporadic colorectal tumors 23, 26, 27 . However, there is no direct evidence that these stem cells give rise to colitis-associated colorectal cancers, and the expression of ISC markers in CAC has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%